Diversity of active root-associated methanotrophs of three emergent plants in a eutrophic wetland in northern China - Cui, Jing (AMB Express, 2020)
Root-associated aerobic methanotrophs play an important role in regulating methane emissions from the wetlands. However, the influences of the plant genotype on root-associated methanotrophic structures, especially on active flora, remain poorly understood. Transcription of the pmoA gene, encoding particulate methane monooxygenase in methanotrophs, was analyzed by reverse transcription PCR (RT-PCR) of mRNA isolated from root samples of three emergent macrophytes, including Phragmites australis, Typha angustifolia, and Schoenoplectus triqueter (syn. Scirpus triqueter L.) from a eutrophic wetland. High-throughput sequencing of pmoA based on DNA and cDNA was used to analyze the methanotrophic community. Sequencing of cDNA pmoA amplicons confirmed that the structure of active methanotrophic was not always consistent with DNA. A type I methanotroph, Methylomonas, was the most active group in P. australis, whereas Methylocystis, a type II methanotroph, was the dominant group in S. triqueter. In T. angustifolia, these two types of methanotroph existed in similar proportions. However, at the DNA level, Methylomonas was predominant in the roots of all three plants. In addition, vegetation type could have a profound impact on root-associated methanotrophic community at both DNA and cDNA levels. These results indicate that members of the genera Methylomonas (type I) and Methylocystis (type II) can significantly contribute to aerobic methane oxidation in a eutrophic wetland.